Perbandingan Model Pembiayaan Syariah Dalam Mendorong Pertumbuhan Ekonomi: Analisis Kualitatif Di Negara-Negara Berpenduduk Mayoritas Muslim - Amania Abdullah; Madian Muhammad Muchlis (Journal Economic Excellence Ibnu Sina, 2024)
This research compares the implementation of Sharia financing models in Malaysia, Indonesia, Bahrain, the United Arab Emirates, and Qatar to analyze their roles in driving economic growth. A qualitative approach is employed to evaluate regulations, infrastructure, and literacy levels related to Sharia financing in these five countries. The results indicate differences in product coverage, market structures, and regulations governing the Sharia financing sector in each country. The more rapid development of Sharia financing in Malaysia and Bahrain correlates with higher economic growth in both nations. This study concludes that a conducive regulatory framework and infrastructure are crucial to promoting the development of Sharia financing, enabling it to play an optimal role in driving economic growth. Integrated policies are needed to strengthen the Islamic financial industry across various Muslim-majority countries.